Bronchodilator Effect of Crataegus azarolus var aronia Unripped Fruit Extracts on Rat’s Tracheal Smooth Muscle - Aveen A. Mohammed; Omar A. M. Al-Habib (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objectives: The present study aimed to investigate the bronchodilator effect of different Crataegus azarolusvar aronia unripped fruit extracts on tracheal smooth muscle of rats and to study the roles of K channels andEDHFs in produced responses.Background: Crataegus is widely used in Kurdistan Region for the prevention of several diseases suchas respiratory, cardiovascular, hypertension …. etc. due to its content of several bioactive compounds likearomatic amines, phenolic acid, flavonoids, and proanthocyanidins.Method: The bronchodilator effects of various Crataegus fruit’s extracts on rat’s tracheal rings and the rolesof K+, Ca2+ channels and EDHFs in bronchodilation using specific blockers.Results: Most of Crataegus fruit’s extracts used showed a potent bronchodilator effect on trachea, in whichthe HME produced a highly significant dilation, followed by methanol and ethyl acetate extracts whichshowed a considerable relaxant effect. The results confirmed that the induced dilation was NO and PGI2dependent, along with activations of KATP and Kir and Kca while Kv plays a minor and limited role.Conclusion: The novel results indicate that HM, M, EA extracts prepared from Crataegus unripped fruitproduce a potent bronchodilator effect, which was NO and PGl2 dependent along with the activation of KATP,Kir and Kca2+ channels.